Sosialisasi “FlowFit” Gerakan Simpel untuk Meningkatkan Kesehatan Sistem Kardiovaskular Ibu PKK Desa Karangan Kecamatan Karanganom Kabupaten Klaten - Kholisna, Arin; Kumalasari, Eni; Nuraini, Habibah; Brata, Nugroho Trisnu; Hendratna, Hendratna (Universitas Negeri Semarang, 2024)
The decrease in physical activity and unhealthy lifestyles cause people in the pre-elderly and elderly age groups to experience various health problems. These problems are experienced by residents of Karangan Village, especially housewives who complain of symptoms of cardiovascular system disorders. This community service program aims to increase awareness and knowledge about the importance of maintaining healthy blood flow through the socialization and education of simple movements called